KARAKTERISASI ISOTERM ADSORPSI DARI ION LOGAM BESI (Fe) PADA TANAH DI KOTA BENGKULU - Hesti Apriyanti; I Nyoman Candra; Elvinawati Elvinawati (University of Bengkulu, 2018)
[CHARACTERIZATION OF THE ADSORPTION FROM IRON METAL IONS ISOTHERM ON THE SOIL IN BENGKULU CITY] Level of micronutrient elements Fe takes part in determining the fertility rate of agricultural land. Continuous oxidation of Fe the soil will cause soil poisoning, due to the soil saturated in absorb of Fe. This research aims to determine the characteristics of the soil, adsorption and its ability in absorption isotherm on Fe metal. Soil samples were taken from the farm in the city of Bengkulu. The characteristics of the soil tested, i.e., water content, pH, and soil type. Adsorption isotherm type is a determination as Langmuir or Freundlich isotherm. Soil sample after it is dried and cleaned and then milled and sieved at 100 mesh sieve. Moisture content is measured by dried in an oven for 24 hours and the measurement of the difference between the initial and the final weight of the soil. Determination of soil pH is measured by the pH meter on the CaCl2, and soil type is determined by calculating the percentage of sand, silt, and clay from the soil. Maximum adsorption capacity is determined from Fe adsorption isotherm after getting the pH, the weight of adsorbent and optimum contact time. Adsorption Isotherm was determined by adsorption of aqueous Fe variation at the concentration of 2.5; 5; 10; 15; 20; and 25 ppm on optimum pH and weight, and stirred at an optimum contact time, then filtered and measured its absorbance with UV-Vis spectrophotometer. Results of research results in the form of moisture content average 23.5%, soil pH value at 5 and soil type, i.e., dusty clay with the dominant form of Isotherm adsorption is a Freundlich isotherm, and the capacity of soil in adsorbing of iron on this research obtained is amounting to 45.6.